The potential status of A1 and A2 variants of bovine beta-casein locus of some indigenous genetic resources reared in Turkey - Şahin, Özcan; Boztepe, Saim (Journal of the Hellenic Veterinary Medical Society, 2022)
The aim of this study was to determine the Beta-Casein gene (CSN2) polymorphism in four domestic cattle breed. The genomic DNA of 374 animals, including Anatolian Black (AB, n= 100), Eastern Anatolian Red (EAR, n= 100), Southern Anatolian Red (SAR, n= 87), Turkish Grey (TG, n= 87), were obtained, and C>A polymorphism in 67th amino acid in the 7th exons of β-casein gene was determined by TaqI enzyme with PCR-RFLP with method. The A1 allele frequency were determined in AB, EAR, SAR and TG as 0.200, 0.195, 0.190 and 0.201, respectively, while the A2 allele frequency were 0.800, 0.805, 0.810 and 0.799, respectively. A1 and A2 allele frequencies were generally calculated as 0.200 and 0.800, respectively. A1A1 genotypes in AB, EAR, SAR and TG breeds were 0.020, 0.070, 0.000 and 0.020, respectively; A1A2 genotypes were 0.360, 0.250, 0.380 and 0.360, respectively; A2A2 genotypes were determined as 0.620, 0.680, 0.620 and 0.620, respectively. The A1A1 genotype frequency has not been detected in the SAR breed. AB, EAR, SAR and TG cattle breeds were calculated as 0.360, 0.250, 0.379 and 0.356 for Ho; 0.320, 0.314, 0.307 and 0.321 for He and 0.380, 0.320, 0.379 and 0.379 for PIC, respectively. EAR and SAR population were not found in Hardy-Weinberg equilibrium (P<0.05). However, AB and TG populations were found in Hardy-Weinberg equilibrium in terms of β-casein gene (P> 0.05). In conclusion, AB, EAR, SAR and TG cattle breeds having A2A2 genotype commonly reared in Turkey are satisfactory and could be used in selection programs as a domestic genetic resource for A2 milk production in the future.